Proceso de comercialización de la Empresa Vi Fashion del cantón Ventanas - Muñoz Miranda, Damaris Dayana (2022)
The commercialization process is about providing customers with what they require to cover their needs and desires, where short and long-term problems are linked, which encourage the establishment of strategies that allow orienting the distribution of goods, therefore the The objective of this work is based on Analyzing the commercialization process of the company "Vi Moda" of the Ventanas canton, a study that is based on evidencing the holistic treatment of the problems present in the boutique, through the systematization of the theoretical foundations, in which, the quantitative aspects and qualitative methodology was applied, through the interview with the owner and the survey of the company's clients. In the conclusions, it is mentioned about the quality of the processes that are executed in the business, evidencing the degree of acceptance related to the attention that is given to the clients and the alternatives that allow to execute improvements in the procedures of distribution of the goods. in which both the owner of the premises and the workers are involved to implement marketing or commercialization strategies.